Management of Retinal Vein Occlusion – Consensus Document - G. Coscas; Anat Loewenstein; Albert J. Augustin; Francesco Bandello; Maurízio Battaglia Parodi; Paolo Lanzetta; Jordi Monés; Marc D. de Smet; G. Soubrane; Giovanni Staurenghi (2011)
Retinal vein occlusion (RVO) can have severe consequences for the people affected by the disease, including visual loss with costly social repercussions. Currently, there is no European consensus with regard to the management of RVO. Following a careful review of the medical literature as well as the data from several clinical trials, a collaborative group of retina specialists put forth practical recommendations based on the best available scientific evidence for the clinical approach to RVO. Taking into consideration the recent advances in diagnostic tools and management options, the present document aims to provide the European ophthalmologists with guidelines for clinical practice to the benefit of their patients.